Dust in the Arctic: a brief review of feedbacks and interactions between climate change, aeolian dust and ecosystems - Meinander, Outi; Uppstu, Andreas; Dagsson-Waldhauserova, Pavla; Groot Zwaaftink, Christine; Juncher Jørgensen, Christian; Baklanov, Alexander; Kristensson, Adam; Massling, Andreas; Sofiev, Mikhail (Frontiers in Environmental Science, 2025)
Climatic feedbacks and ecosystem impacts related to dust in the Arctic include direct radiative forcing (absorption and scattering), indirect radiative forcing (via clouds and cryosphere), semi-direct effects of dust on meteorological parameters, effects on atmospheric chemistry, as well as impacts on terrestrial, marine, freshwater, and cryospheric ecosystems. This review discusses our recent understanding on dust emissions and their long-range transport routes, deposition, and ecosystem effects in the Arctic. Furthermore, it demonstrates feedback mechanisms and interactions between climate change, atmospheric dust, and Arctic ecosystems.